The Effect of Financial Performance on Firm Value with Corporate Social Responsibility as Moderated Variables - Nafasati, Febrina; Hilal, Muhammad (Economics and Business Solutions Journal, 2021)
The purpose of this study is to examine financial performance on the firm value and to examine corporate social responsibility in moderating the relationship between financial performance and firm value. This study examines the effects of financial applications on industrial figures and examines corporate social responsibility in moderating the ties of financial applications on industrial figures.This study was conducted on 28 banking companies listed on the Indonesia Stock Exchange (IDX) during the 2016 2018 period using secondary data. The samples were selected using the purposive sampling method, with a total of 84 companies. This study's data analysis technique was the simple regression analysis and moderated using Wrap PLS 7 with the independent variable of financial performance, the dependent variable of firm value, and the moderating variable of corporate social responsibility.The results showed that financial performance affected firm value, while corporate social responsibility was able to moderate financial performance on firm value.